STALIN’S RESTORATION OF THE “SOCIALIST LEGALITY” IN CHECHEN-INGUSHETIA (1938-1940) - Osmaev, Abbaz Dogievic; Dendiev, Kazbek Gilanievic (History, Archeology and Ethnography of the Caucasus, 2021)
The article explores a poorly-studied aspect of repressive politics – the so-called restoration of revolutionary law and order in the USSR in the late 1930s – on the example of law enforcement agencies of Chechen-Ingushetia. The study aims to reconstruct the implementation of the Stalinist correction in repressive practice in the region on the basis of materials from central and regional archives, previously published documents, and to identify the role of party and law enforcement agencies in it. The object of the study is the repressive policy of the Soviet state in the 1930s in the Chechen-Ingush Autonomous Soviet Socialist Republic (hereinafter as CHIASSR). The subject of the study is the implementation of the changes made by the center in the repressive policy in the late 1938 – early 1940s in the republic. The study applies general scientific methods of analysis and synthesis, classification, comparison and analogy, historicism, objectivity and consistency. The source base of the work is archival and published documents, in particular, records of bureau sessions, plenums of the Chechen-Ingush Regional Committee of the CPSU from the Archival Department of the Government of the Chechen Republic, State Archive of the Russian Federation (hereinafter as SARF) and other archives of the country. The scientific novelty of the study lies in the fact that a study of the period of political repression was conducted on the example of the Chechen-Ingush ASSR in late 1938 – early 1940, when the restoration of the rule of law was officially proclaimed. In reality, the repressions continued, although they peaked in 1937-1938; the role of the party and state bodies in the implementation of the directives of the center is analyzed. The theoretical and practical significance of the work is determined by the fact that the research materials allow to expand the scientific understanding of political repressions in Chechen-Ingushetia. The provisions and conclusions of the work can be used in the activities of educational organizations for the study of the Soviet history. The study conducted reveals a certain algorithm of Stalin’s actions to “restore” revolutionary legality.